B(OH)4- and CO32- do not compete for incorporation into aragonite in synthetic precipitations at pHtotal 8.20 and 8.41 but do compete at pHtotal 8.59 - Castillo Alvarez, Maria Cristina; Penkman, Kirsty; Kroger, Roland; Finch, Adrian Anthony; Clog, Matthieu; Hathorne, Ed; Allison, Nicola (Geochimica et Cosmochimica Acta, 2024)
This work was supported by the UK Natural Environment Research Council (NE/S001417/1) to NA, KP, RK, MC and AF. We thank Gavin Peters, University of St Andrews, for assistance with BET analyses and Adam Kerrigan, University of York, for support with scanning electron microscopy. Coral skeletal B/Ca (effectively B/CO32–), in combination with boron isotopic composition (δ11B), has been used to reconstruct the dissolved inorganic carbon chemistry of coral calcification media and to explore the biomineralisation process and its response to ocean acidification. This approach assumes that B(OH)4−, the B species incorporated into aragonite, competes with dissolved inorganic carbon species for inclusion in the mineral lattice. In this study we precipitated aragonite from seawater in vitro under conditions that simulate the compositions of the calcification media used to build tropical coral skeletons. To deconvolve the effects of pH and [CO32–] on boron incorporation we conducted multiple experiments at constant [CO32–] but variable pH and at constant pH but variable [CO32–], both in the absence and presence of common coral skeletal amino acids. Large changes in solution [CO32–], from < 400 to >1000 µmol kg−1, or in precipitation rate, have no significant effect on aragonite B/Ca at pHtotal of 8.20 and 8.41. A significant inverse relationship is observed between solution [CO32–] and aragonite B/Ca at pHtotal = 8.59. Aragonite B/Ca is positively correlated with seawater pH across precipitations conducted at multiple pH but this relationship is driven by the effect of pH on the abundance of B(OH)4– in seawater. Glutamic acid and glycine enhance the incorporation of B in aragonite but aspartic acid has no measurable effect. Normalising aragonite B/Ca to solution [B(OH)4–] creates KDB(OH)4− which do not vary significantly between pH treatments. This implies that B(OH)4– and CO32– do not compete with each other for inclusion in the aragonite lattice at pHtotal 8.20 and 8.41. Only at high pH (8.59), when [B(OH)4–] is ...